Analysis of N, N‐dimethylamphetamine in wastewater – a pyrolysis marker and synthesis impurity of methamphetamine. Issue 10 (20th July 2018) - Been, Frederic; O'Brien, Jake; Lai, Foon Yin; Morelato, Marie; Vallely, Peter; McGowan, Jenny; van Nuijs, Alexander L. N.; Covaci, Adrian; Mueller, Jochen F.
Abstract: The increased availability of high purity crystalline methamphetamine (MA) in Australia raised concerns because of high dosages and its potential consumption through inhalation. The present work investigates the possibility of using wastewater levels of N, N‐dimethylamphetamine (DMA), a pyrolysis by‐product, as an indirect indicator of MA smoking. A dedicated liquid chromatography quadrupole‐time‐of‐flight mass spectrometry (LC–QToF–MS) method was set up to detect and quantify DMA in wastewater samples. Wastewater samples were collected from 8 locations across Australia during the period 2011–2016. Data about the abundance of DMA in MA seizures as well as in residues from drug paraphernalia were obtained from forensic laboratories in Australia. DMA/MA ratios measured in wastewater ranged from 0.0001 to 0.09 (median 0.007). DMA/MA ratios in bulk seizures are generally below 0.0025, with a median value of 0.0004, whilst residues in paraphernalia ranged from 0.031 to 3.37. DMA/MA ratios in wastewater decreased between 2011 and 2016, in parallel to an increase in MA loads. Furthermore, wastewater analyses highlighted a strong positive correlation between DMA/MA ratios and per capita MA use (Pearson's correlation ρ= 0.61, p ‐value <0.001). Nonetheless, geographical specificities could be highlighted between the investigated locations. The obtained data could help authorities detect hot spots of drug use as well as to plan specific intervention campaigns to tackle the issue. In future, simultaneous analysis of DMA and MA in both wastewater and seizures could improve our understanding about MA use and its consumption patterns. Abstract : N, N‐dimethylamphetamine (DMA) was measured in wastewater samples Levels of DMA measured in wastewater were higher compared to methamphetamine seizures Simultaneous analysis of DMA and methamphetamine (MA) in wastewater and seizures could help better understand MA use